Defeasible logic programming: language definition, operational semantics, and parallelism - Garcia, Alejandro Javier (Journal of Computer Science & Technology, 2001)
This thesis defines Defeasible Logic Programming and provides a concrete specification of this new language through its operational semantics. Defeasible Logic Programming, or DeLP for short, has been defined based on the Logic Programming paradigm and considering features of recent developments in the area of Defeasible Argumentation. DeLP relates and improves many aspects of the areas of Logic Programming, Defeasible Argumentation, Intelligent Agents, and Parallel Logic Programming